USM AND IAHR TO ORGANISE WATER MANAGEMENT CONGRESS 2017 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 12 April 2016 – Universiti Sains Malaysia (USM) continues to widen its international network in the field of water management through cooperation with strategic partners in further championing sustainability.